Factors contributing to the success of crowdfunding: the Malaysian case - Rahman, Maya Puspa; Duasa, Jarita; Mustaffa Kamil, Nazrol Kamil (2016)
Crowdfunding is getting the world's attention due to the fact that it is particularly useful to support the development of new ideas and initiatives that cannot be funded by traditional mode of financing such as financing from financial institutions. Being globally recognized as the next best alternative for entrepreneurs to raise funds, it is highly important to discover the factors contributing to the success of raising funds through this mechanism. Based on interviews with major industry players, this research critically address the issues associated with crowdfunding and presents the factors mostly important for project owners or entrepreneurs to consider before engaging in raising funds through the crowdfunding platforms, in Malaysia. Apart from enriching the literature in crowdfunding, this research is expected to spur awareness on the importance and implications of crowdfunding in the Malaysian capital market.